FROM EUROPE TO LOMBOK: THE DISCOURSE OF LOMBOK TOURISM IN THE NOVEL MEDULLA SINCULASIS - Satrya HD, Dharma (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
This article discusses the discourse of Lombok tourism in Paox Iben's novel Medulla Sinculasis. In Lombok, discourse on tourism was initiated by Tuan Guru Bajang, a religious scholar, after he was elected the governor of West Nusa Tenggara, Indonesia, in 2008. Within this context, the novel Medulla Sinculasis is discussed. The novel constructs an understanding of Lombok as a tourism destination, beginning with Europe. In this story, Nuruda is driven to visit Lombok after seeing a painting titled Medulla Sinculasis being auctioned at the Van Gogh Museum in the Netherlands. After returning to Indonesia from Europe, Nuruda decides to travel directly to Lombok and meet Husin Nanang, the painter. His meeting with Husin Nanang, as well as the situation in Ampenan City, leads Nuruda on a transformation from tourist to social activist, fighting to protect the rights and promote the interests of marginal groups. Nuruda's struggle is ultimately unsuccessful, and he is killed in a hit-and-run. The Lombok in this novel is part of the discourse from the 2000s and 2010s, a period that was dominated by the economisation of Lombok. The novel Medulla Sinculasis may be seen part of this dominant discourse, and thus having the economisation of Lombok as part of its agenda.